Effect of Botanical Pesticides on Inhibiting Colletotrichum sp. Causing Anthracnose in Avocado (Persea americana Mill.) In Vitro - Anisa Rahman Rusiati; Feskaharny Alamsjah; Riska; Suwirmen (Jurnal Penelitian Pendidikan IPA, 2026)
Anthracnose caused by Colletotrichum sp. is a major postharvest disease of avocado (Persea americana Mill.) that leads to significant economic losses during storage. This study aimed to evaluate the antifungal efficacy of essential oil-based botanical pesticides derived from lemongrass (Cymbopogon nardus L.), cinnamon (Cinnamomum burmannii L.), and wild betel (Piper aduncum L.) against Colletotrichum sp. in vitro. The experiment was arranged in a Completely Randomized Design (CRD) with nine treatments and three replications, using essential oil concentrations up to 1000 ppm in both single and combined formulations. Antifungal activity was assessed based on colony diameter and fungal biomass, and data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s New Multiple Range Test (DNMRT). All treatments significantly inhibited fungal growth compared to the control. The smallest colony diameter was recorded in the lemongrass treatment (12.80 mm), with the highest inhibition rate of 85.77%. The lowest fungal biomass was observed in the cinnamon treatment (20 mg). These results demonstrate very strong antifungal activity of the tested essential oils.This study highlights the novelty of utilizing locally sourced essential oils as botanical pesticide formulations targeting Colletotrichum sp., suggesting their potential as environmentally friendly alternatives for sustainable postharvest disease management.